2005
DOI: 10.1002/uog.2686
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to first‐trimester screening for early pre‐eclampsia combining serum PP‐13 and Doppler ultrasound

Abstract: Objective To investigate the value of maternal serum placental protein 13

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
186
3
17

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(218 citation statements)
references
References 18 publications
3
186
3
17
Order By: Relevance
“…One study reported a PP13 median of 66.6 pg/ml for controls, [16] and another presented medians by week of gestation for weeks [11][12][13]; with values of 53.5, 63.1, 65.7 pg/ml, respectively; [19] while a study of nulliparous women reported slightly higher levels of PP-13 (77.3 pg/ml). [17] In comparison, median level of PP13 among controls in the in-house study was 53.5 (IQR; 37.7-71.8) pg/ml for all woman, 54.7 (IQR; 39.8-72.1) pg/ml for nulliparous women and 53.9, 54.0, 52.5 pg/ml for gestational week 11-13, respectively.…”
Section: Systematic Review and Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…One study reported a PP13 median of 66.6 pg/ml for controls, [16] and another presented medians by week of gestation for weeks [11][12][13]; with values of 53.5, 63.1, 65.7 pg/ml, respectively; [19] while a study of nulliparous women reported slightly higher levels of PP-13 (77.3 pg/ml). [17] In comparison, median level of PP13 among controls in the in-house study was 53.5 (IQR; 37.7-71.8) pg/ml for all woman, 54.7 (IQR; 39.8-72.1) pg/ml for nulliparous women and 53.9, 54.0, 52.5 pg/ml for gestational week 11-13, respectively.…”
Section: Systematic Review and Meta-analysismentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15] However, less remarkable predictive properties have been reported in recent studies, with some describing a potential role of PP13 levels for predicting preeclampsia or small for gestational age (SGA) in combination with other biomarkers. [9,12,15] Variation in study design, population characteristics, numbers of cases and reporting of the diagnostic accuracy of PP13, have made it difficult to interpret the clinical significance of these results.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, clinical history, maternal serum biochemistry and uterine artery Doppler sonography before 14 weeks are being investigated. [4][5][6][7] In the second trimester, uterine artery Doppler can claim a detection rate (DR) of only 63.1% for a high (25%) false-positive rate (FPR). 8 First-trimester uterine artery Doppler studies have been shown to have high sensitivity but poor specificity, with a high FPR.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that patients who subsequently developed preeclampsia had lower maternal serum PP13 concentrations in the first trimester than women who had a normal pregnancy outcome [2,6].…”
Section: Mutations In the Lgals13 Gene And Their Impact On The Use Ofmentioning
confidence: 99%
“…Other analytes which appear promising include activin A, inhibin A, PAPP-A, and PP13 [1]. Recent studies have also suggested that it may be valuable to combine the results of biochemical tests with uterine artery Doppler velocimetry in the first and second trimesters [1][2]. This workshop was organized to highlight recent discoveries in the field.…”
Section: Introductionmentioning
confidence: 99%